Hybrid and Online Peer Group Grading: Adding Assessment Efficiency While Maintaining Perceived Fairness. Issue 4 (2nd October 2021) - Vander Schee, Brian A.; Birrittella, Tim Dugan
ABSTRACT: The rate of transition to online instruction in higher education was accelerated by the new reality of the global pandemic, COVID-19. As a result, faculty must adapt by being more efficient to manage more students with less resources and even less personal contact for the foreseeable future. Efficiency can be gained by using group assignments and peer group grading. Peer group grading reduces assessment time although students may be concerned about having their work graded fairly by other students. The peer group grading process and grades are analyzed against the instructor grades over a two-year period. Results demonstrate no significant difference in peer group grades and instructor grades for pre-COVID-19 hybrid and post-COVID-19 online courses. Student survey results also show that students perceive peer group grading as fair in both course formats. Therefore, instructors can feel confident about using peer group grading as a fair and time saving assessment tool.